A complete system modelling of Piezoelectric Energy Harvester (PEH) with Silicon Carbide (SiC) Used as cantilever base - Mohd Kazim, Mohd Nor Fakhzan; Raman, Selvanayakan; Shafie, Muhammad Hafiz; Mohd Nasir, Nashrul Fazli; Abdul Muthalif, Asan Gani (Universiti Teknologi Malaysia, 2014)
Silicon carbide (SiC) is a material that possesses hardness and robustness to operate under high temperature condition. This work is a pilot in exploring the feasibility of cubic piezo element on the SiC wafer with integrated proof mass as horizontal cantilever with perpendicular displacement with respect to the normal plane. With the advance of electronic circuitry, the power consumption is reduced to nano-watts. Therefore, harvesting ambient energy and converting into electrical energy through piezoelectric material will be useful for powering low power devices. Resonance is a property which able to optimize the generated output power by tuning the proof masses. The damping ratio is a considerable parameter for optimization. From analytical study, small damping ratio will enhance the output power of the piezoelectric energy harvester (PEH). This paper will present mathematical modelling approach, simulation verification and the conditional circuit named versatile precision full wave rectifier.